Elderly Male With Cardiovascular-Related Comorbidities Has a Higher Rate of Fatal Outcomes: A Retrospective Study in 602 Patients With Coronavirus Disease 2019 - Zhan, Xiao-Yong; Li, Liang; Hu, Yuhai; Li, Qiang; Kong, Huimin; Ng, Margaret H. L.; Chen, Chun; He, Yulong; Huang, Bihui; Yang, Mo (Frontiers in Cardiovascular Medicine, 2021)
Elderly with comorbidities have shown a higher rate of fatal outcomes when suffering COVID-19. However, delineation of clinical significances of hematologic indices and underlying comorbidities in the progression and outcome of COVID-19 remains undefined. 602 COVID-19 patients with established clinical outcomes (discharged or deceased) from Hankou hospital of Wuhan, China between January 14, 2020 and February 29, 2020 were retrospectively analyzed. Of 602 patients with COVID-19, 539 were discharged and 63 died in hospital. The deceased group showed higher leukocyte and neutrophil counts but lower lymphocyte and platelet counts. Longer activated partial thromboplastin time (APTT) and prothrombin time (PT), as well as higher D-Dimer and C-reactive protein levels, were found in non-survivors. Our observations suggest that these parameters could serve as potential predictors for the fatal outcome and in the discharged group. Higher neutrophil count, and D-dimer level but lower lymphocyte was associated with longer duration of hospitalization. A multivariable Cox regression analysis showed that higher neutrophil count, prolonged PT, and low lymphocyte count were risk factors for patients with COVID-19. Also, we found an association of lower lymphocyte count and higher C-reactive protein levels with the elderly group and those with cardiovascular-related comorbidities. The significantly different hematologic profiles between survivors and non-survivors support that distinct hematologic signatures in COVID-19 patients will dictate different outcomes as a prognostic marker for recovery or fatality. Lymphopenia and aggressive inflammatory response might be major causes for fatal outcomes in the elderly male and especially those with cardiovascular-related comorbidities.